Security Performance of LoRaWAN Servers using Advanced Encryption Standard - adi, Puput Dani Prasetyo (Internet of Things and Artificial Intelligence Journal, 2023)
One of the essential components in LoRaWAN is managing the server with all existing components, including Device Management, Data forwarding, Network security, and real-time network monitoring. It is necessary to manage the uplink and downlink of the LoRaWAN server and maintain the quality of data transmission from the LoRa end node to the LoRaWAN server. Depending on the service provider, the LoRaWAN Server provides space for payload, uplink, and downlink data. How many times in a day, week, month, or even year? This discussion depends on the LoRaWAN server provider. Some are open sources, and some provide free uplink and downlink services. Settings on the LoRaWAN Server will determine how much data will enter the server or the network size. Security is also an essential parameter, e.g., encryption or authentication, supported by the feature requirements used on the server, which will determine the type of communication that LoRa will apply, for example, multi-communication or analysis data. Centralized management, Security, scalability, and cost-effectiveness are essential parameters if LoRaWAN is managed well.